2020
DOI: 10.3390/ijerph17165825
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Perceived Unjust Treatment in Unmet Needs for Primary Care Among Finnish Roma Adults

Abstract: The main goal in developing services is to guarantee equal access to healthcare services that are suited to the patients’ needs. Previous studies have shown that the Roma are more likely to experience unjust treatment in health services than the general population. This study examines the association between perceived unjust treatment in healthcare and self-assessed unmet need for primary care provided by general practitioners (GPs) and nurses among the Finnish Roma. The data from the Finnish Roma Wellbeing St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 47 publications
1
1
0
Order By: Relevance
“…The particular concern about children's health found in this research has earlier been described similarly concerning immunization uptake (46). In line with other studies in different Roma populations, we identified an interplay of day-to-day priorities, ignorance of long-term implications, fear of a diagnosis, distance to healthcare facilities, low levels of health literacy, discrimination-fueled distrust of healthcare providers, and a strong masculine culture to negatively influence health behavior (45,(47)(48)(49). Our study is the first, however, to relate this interplay specifically to CRDs and potentially other chronic diseases.…”
Section: Interpretation Of Findings In Relation To Literaturesupporting
confidence: 87%
See 1 more Smart Citation
“…The particular concern about children's health found in this research has earlier been described similarly concerning immunization uptake (46). In line with other studies in different Roma populations, we identified an interplay of day-to-day priorities, ignorance of long-term implications, fear of a diagnosis, distance to healthcare facilities, low levels of health literacy, discrimination-fueled distrust of healthcare providers, and a strong masculine culture to negatively influence health behavior (45,(47)(48)(49). Our study is the first, however, to relate this interplay specifically to CRDs and potentially other chronic diseases.…”
Section: Interpretation Of Findings In Relation To Literaturesupporting
confidence: 87%
“…It has been suggested that Roma "nonadherence norms" to medical recommendations are less likely to be present in environments that hold less anti-Roma views (52). This underlines the importance to support non-Roma HPs in their interaction with Roma, as expressed in previous studies (47)(48)(49)51). Considering that most CRD-related care in Greece takes place in hospital settings (52), the importance of welcoming interactions should be duly noted.…”
Section: Interpretation Of Findings In Relation To Literaturementioning
confidence: 85%